From Case Studies to Cohort of Patients: Automating FSI Simulations to Uncover Downstream Effects of Ascending Aortic Grafts - Ione Ianniruberto; Davide Astori; Simone Saitta; Davide Milesi; Pablo Villar Calle; Mario Gaudino; Leonard N. Girardi; Jay D. Humphrey; Jonathan W. Weinsaft; Emiliano Votta; Alberto Redaelli (Annals of Biomedical Engineering, 2026)
Purpose Open surgical repair with replacement of the diseased segment by a synthetic Dacron graft remains the standard treatment for ascending thoracic aortic aneurysms and dissections. However, post-operative sequelae, including dissection of the descending aorta (DA), have been reported and are often attributed to the mechanical compliance mismatch between the rigid graft and native aortic tissue. This mismatch can significantly alter downstream hemodynamics, potentially promoting adverse vascular remodeling and accelerating disease progression. Methods A fully automated patient-specific fluid–structure interaction (FSI) pipeline was developed to evaluate hemodynamic changes following graft implantation based on cardiac imaging: aortic 3D anatomy is reconstructed from Magnetic Resonance Angiography; aortic wall mechanics are described as anisotropic hyperelastic, with region-specific parameters calibrated from Cine-MRI-derived wall thickness and compliance data; blood flow is modeled using inlet velocity profiles derived from 4D flow MRI and Windkessel outlet conditions tuned to in vivo pressures. The computational workflow, implemented in the open-source software SimVascular, comprised three stages: (i) computational fluid dynamics simulation to determine blood pressures, (ii) structural analysis for prestress estimation, and (iii) FSI simulation coupling fluid and solid responses. It was applied to five patients whose images were collected pre-operatively, and post-operatively. Pre-operative and post-operative scenarios were then compared to assess whether the compliance mismatch due to the presence of the ascending graft alters the hemodynamic and biomechanics in the DA. Results The proposed framework successfully performed standardized, automated FSI simulations for all patients. Comparison between pre- and post-operative states revealed preliminary evidence of graft-associated flow remodeling, with consistent increases in flow-induced wall shear stress (WSS), oscillatory shear index, and Time Averaged WSS (TAWSS) in the aortic isthmus, which is commonly associated with post-operative dilation. Additionally, a topological analysis of WSS manifolds demonstrated a redistribution of fixed points from the ascending to the isthmus region after graft implantation, suggesting localized hemodynamic disturbances which may correlate with adverse biological responses. Conclusion This automated framework enables large-scale patient-specific FSI analyses and highlights preliminary biomechanical changes induced by aortic grafts. The high values of WSS observed in the isthmus region suggest that next-generation compliant grafts should be designed to mitigate downstream disease progression by lowering WSSs.

Effects of local management and landscape factors on taxonomic and functional diversity of multiple taxa in managed grasslands - Matteo Conti; Andrea Dalpasso; Alberto Mattia Nodari; Isabel Cantera; Benedetta Barzaghi; Mattia Brambilla; Andrea Ferrari; Gentile Francesco Ficetola; Simone Giachello; Elia Lo Parrino; Valeria Messina; Carlo Polidori; et al. (Agriculture, Ecosystems & Environment, 2026)

Left ventricle diastolic vortex ring characterization in ischemic cardiomyopathy: insight into atrio-ventricular interplay - Alessandra Riva; Simone Saitta; Francesco Sturla; Giandomenico Disabato; Lara Tondi; Antonia Camporeale; Daniel Giese; Serenella Castelvecchio; Lorenzo Menicanti; Alberto Redaelli; Massimo Lombardi; Emiliano Votta (Medical & Biological Engineering & Computing, 2024)

Use of infrared thermography from a crewed aerial vehicle for remote sensing of tropical pasture areas with different levels of afforestation - Alexandre Rossetto Garcia; Alberto Carlos de Campos Bernardi; José Ricardo Macedo Pezzopane; Veronica Redaelli; Fabio Luzi; Nicolle Laurenti; Lucas Perassoli Menegazzo; Christine Elisabeth Grudzinski; Paulo Cerqueira dos Santos Junior; Antonio Vinicius Corrêa Barbosa (Computers and Electronics in Agriculture, 2023)

Patient-Specific Bicuspid Aortic Valve Biomechanics: A Magnetic Resonance Imaging Integrated Fluid–Structure Interaction Approach - Monica Emendi; Francesco Sturla; Ram P. Ghosh; Matteo Bianchi; Filippo Piatti; Francesca R. Pluchinotta; Daniel Giese; Massimo Lombardi; Alberto Redaelli; Danny Bluestein (Annals of Biomedical Engineering, 2021)

Functional and Biomechanical Effects of the Edge-to-Edge Repair in the Setting of Mitral Regurgitation: Consolidated Knowledge and Novel Tools to Gain Insight into Its Percutaneous Implementation - Francesco Sturla; Alberto Redaelli; Giovanni Puppini; Francesco Onorati; Giuseppe Faggian; Emiliano Votta (Cardiovascular Engineering and Technology, 2015)

Influence of Mitral Valve Anterior Leaflet in vivo Shape on Left Ventricular Ejection - Annalisa Dimasi; Emanuele Cattarinuzzi; Marco Stevanella; Carlo A. Conti; Emiliano Votta; Francesco Maffessanti; Neil B. Ingels; Alberto Redaelli (Cardiovascular Engineering and Technology, 2012)

Aortic Valve Repair via Neo-Chordae Technique: Mechanistic Insight Through Numerical Modelling - Emiliano Votta; Luca Paroni; Carlo A. Conti; Alessandra Pelosi; Andrea Mangini; Paolo D’Alesio; Riccardo Vismara; Carlo Antona; Alberto Redaelli (Annals of Biomedical Engineering, 2012)

Synthetic dataset generation for the analysis and the evaluation of image-based hemodynamics of the human aorta - Umberto Morbiducci; Raffaele Ponzini; Giovanna Rizzo; Marco Evanghelos Biancolini; Francesco Iannaccone; Diego Gallo; Alberto Redaelli (Medical & Biological Engineering & Computing, 2012)

Mitral Valve Patient-Specific Finite Element Modeling from Cardiac MRI: Application to an Annuloplasty Procedure - Marco Stevanella; Francesco Maffessanti; Carlo A. Conti; Emiliano Votta; Alice Arnoldi; Massimo Lombardi; Oberdan Parodi; Enrico G. Caiani; Alberto Redaelli (Cardiovascular Engineering and Technology, 2011)

Quantitative Analysis of Bulk Flow in Image-Based Hemodynamic Models of the Carotid Bifurcation: The Influence of Outflow Conditions as Test Case - Umberto Morbiducci; Diego Gallo; Raffaele Ponzini; Diana Massai; Luca Antiga; Franco M. Montevecchi; Alberto Redaelli (Annals of Biomedical Engineering, 2010)

A Bioreactor with Compliance Monitoring for Heart Valve Grafts - Riccardo Vismara; Monica Soncini; Giuseppe Talò; Luca Dainese; Anna Guarino; Alberto Redaelli; Gianfranco B. Fiore (Annals of Biomedical Engineering, 2010)

In Vivo Quantification of Helical Blood Flow in Human Aorta by Time-Resolved Three-Dimensional Cine Phase Contrast Magnetic Resonance Imaging - Umberto Morbiducci; Raffaele Ponzini; Giovanna Rizzo; Marcello Cadioli; Antonio Esposito; Francesco De Cobelli; Alessandro Del Maschio; Franco Maria Montevecchi; Alberto Redaelli (Annals of Biomedical Engineering, 2009)

Mesh updating in fluid-structure interactions in biomechanics: An iterative method based on an uncoupled approach - Gabriele Dubini; Alberto Redaelli (Annals of Biomedical Engineering, 1997)